ANALISIS MINAT BELAJAR DAN BAKAT TERHADAP HASIL BELAJAR MATEMATIKA SISWA - Fadillah, Ahmad (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2016)
The purpose of this study was to determine  whether  there  is  influence students' interest in learning and talent of the student learning outcomes. This study uses a quantitative survey with correlation techniques. This research was conducted at SMPN 18 Tangerang, the study population was as many as 250 students of class VII and sample as many as 153 students. Instruments in this study tests and questionnaires or questionnaire. Of multiple correlation analysis obtained t count = 23.208> t table =  3.06  for  the  5%  significance  level  and regression  analysis  obtained,  which  means the interest in learning, gifted students and learning    outcomes    have    a    significant relationship and shows that interest in learning and talent students are influential the results of students' mathematics learning.